The 'fake' challenge. Content and diffusive processes of Blue Whale, Momo Game and Jonathan Galindo Challenge - Carlotta Antonelli (2023)
The article intends to reflect on online practices, considered as high-tech adventures aimed at satisfying (also) psychological needs (Hung-Yi Lu 2008), focusing on some specific social media challenges, i.e. those digital contents structured around playful, skill or courage challenges, which invite individual or group users to creatively (re)interpret a performance and share it on their social channels (Burgess et al., 2018; Schlaile et al., 2018). This is a hybrid form (Burgess et al., 2018) of digital content in which viral intent is intertwined with the imitative ambition prompted by memes (Dawkins, 1976, Blackmore, 2000; Schmid, 2004). Among the online challenges considered, some take the form of 'fake' challenges, as they are the result of the contamination between fake news, understood as false information or partial truths circulated by or through the media (Dentith, 2017) and social media challenges. Fake challenges are thus constructed or amplified by the media system, but with little or no online circulation. These include in particular challenges such as Blue Whale, Jonathan Galindo and Momo Game (Giordano, 2020), selected because they belong to the broader sphere of suicide games, i.e. challenges that directly or indirectly invite suicide. Although there is no evidence that suicide games really exist, the media's account of them, at least in Italy, has fuelled a real moral panic (Cohen, 1972) and activated concerns and institutional reactions at various levels (Bada, Clayton, 2020). The objectives of this work are to identify the elements of recursiveness of the alleged challenges in their journalistic representation and to reconstruct their path of birth, evolution and diffusion in the media system concerning them, in light of the logic of newsworthiness in journalistic and media narratives (Wolf, 1994; Edgerly and Vraga 2020; ) and considering as a theoretical framework the recent literature on the characteristics and generative processes of fake news (Jaster, Lanius, 2018), understood not only ...